CORRIGENDUM TO “INTEGRATION PLANNING BETWEEN COMPONENTS OF TYPE B BUS STATION SUKOREJO ” (Journal of Applied Engineering Science, 2024)
CLARIFICATIONThe  author’s  name Dessy Angga Afriyanti was misprinted  within  the article  in  subject published  in  22(2024)1,  1181,  223-233, DOI:10.5937/jaes0-45719. Authors’ name should be corrected as follows: Dessy Angga AfriantiThis addition does not affect the original paper. We apologize for any inconvenience that this may have caused.